Bibliometric Evaluation of Work-Life Balance Research Developments from A Global Perspective - Fitriyani, Desy; Iskandar, Yusuf (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Maintaining a healthy work-life balance has emerged as a pressing concern in contemporary society, given the relentless pace of the modern world and the relentless pursuit of career success. This paper employs a bibliometric approach to delve into the landscape of work-life balance research, delving into trends, pivotal themes, and collaboration dynamics among scholars. The methodology hinges on meticulous data collection from esteemed academic databases, followed by comprehensive analysis facilitated by bibliometric software. The findings underscore a burgeoning interest in work-life balance inquiry, underscored by a dual focus on the detrimental repercussions of work-family conflict and the advantageous outcomes of attaining equilibrium. The analysis sheds light on influential authors shaping the discourse, pivotal research themes driving the field forward, and prospective avenues for further exploration. These insights hold significance for academia, industry practitioners, and policymakers alike. By unpacking the implications of this research, organizations, individuals, and society stand to gain. It underscores the imperative of fostering work-life balance not only for individual well-being but also for optimizing organizational effectiveness. Moreover, the paper emphasizes the nuanced interplay between work and personal life, advocating for strategies that facilitate harmony between the two realms. Recognizing the multifaceted nature of work-life balance, it calls for tailored interventions and policies that acknowledge diverse needs and preferences. By fostering an environment conducive to balance, organizations can enhance employee satisfaction, productivity, and retention rates. Simultaneously, individuals can lead more fulfilling lives characterized by holistic well-being and fulfillment across various domains. In essence, this research contributes to a deeper understanding of work-life balance dynamics, offering actionable insights for stakeholders across different spheres.